Corpo, linguagem e educação física : o limite culturalista sob a prespectiva do filósofo José Nuno Gil - Costa, Marcelo Adolfo Duque Gomes da (2014)
This work operates with the thesis that a new look at the body (in which it is also a producer of knowledge) could help us to better understand the knowledge we produce. Body that has been thought of, from modernity (for scientific reason, above all for Western rationality), as always having a secondary role, if compared to the importance attributed to the intellectual plane. The theoretical tool to be used is the philosophy (of the body) by José Nuno Gil, in order to offer the field of physical education a contribution to what Professor Mauro Betti called "dilemma of the cultural turn". In this endeavor, we discussed the following concept of the naked image philosopher; small perceptions; body inscription; infralanguage; body awareness; body of consciousness; body of thought; body space; interior space. From them we try to extract implications for physical education, with focus, more specifically, on the problematizations that involve the relationship between body, knowledge and language.